1997
DOI: 10.1080/002075997400629
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Interactive Acculturation Model: A Social Psychological Approach

Abstract: The ® rst part of this paper proposes a continuum of ideological premises that seeks to account for the broad range of immigrant integration policies adopted by Western democratic states. In the second part, a review of Social Psychological models of immigrant acculturation strategies demonstrates the need to explain more clearly the interactive nature of immig rant and host community relations. The Interac tive Acculturation Mode l (IAM) presented next proposes that relational outcomes are the product of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,108
4
166

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,238 publications
(1,345 citation statements)
references
References 28 publications
38
1,108
4
166
Order By: Relevance
“…Attitudes and behavior of the majority group may also strongly influence those of minority members. In this vein, Bourhis et al (1997) have shown that, in addition to acculturation strategies employed by immigrants, the host society's preference for immigrant's acculturation strategies may be just as influential on the outcomes of the acculturation process.…”
Section: Importance Of Measuring Perceptions Towards Diversitymentioning
confidence: 99%
“…Attitudes and behavior of the majority group may also strongly influence those of minority members. In this vein, Bourhis et al (1997) have shown that, in addition to acculturation strategies employed by immigrants, the host society's preference for immigrant's acculturation strategies may be just as influential on the outcomes of the acculturation process.…”
Section: Importance Of Measuring Perceptions Towards Diversitymentioning
confidence: 99%
“…Minority and majority attitudes towards acculturation can either be concordant and give rise to consensual relations between majorities and minorities (especially when both groups agree on integration or assimilation as preferred modes of acculturation), or discordant, evidenced by a mismatch between minority preferences and majority expectations, leading to problematic or even conflictual relationships (Bourhis et al, 1997). The relational outcomes of a mismatch of intergroup definitions of acculturation orientations include, for migrants, heightened acculturative stress, and, for members of the receiving society, stereotyping and discriminatory behaviors, for example in educational or health care institutions, at the workplace, in housing decisions or in encounters with the police.…”
Section: Intergroup Approaches To Acculturation and Multiculturalismmentioning
confidence: 99%
“…In the wake of the intergroup perspective developed by the Interactive acculturation model (Bourhis et al, 1997), recent research has examined the effects of match and mismatch between acculturation orientations held by migrant groups and receiving societies (van Oudenhoven, Ward, & Masgoret, 2006;Roccas et al, 2000;Zagefka & Brown, 2002).…”
Section: Intergroup Approaches To Acculturation and Multiculturalismmentioning
confidence: 99%
“…In Western contexts (both North American and Western European) the acculturation of immigrant or minority groups is studied . However, depending on the immigration and integration policies of the host nation, the mainstream culture might influence the acculturation strategy adopted by the immigrant group (Bourhis, Moïse, Perreault, & Senécal, 1997) .…”
Section: Acculturation and Identitymentioning
confidence: 99%